The Wordsworth Dictionary Of Military Biography (Wordsworth Reference) - Windrow, Martin and Mason, Francis K; General; Military Biography; Soldiers (Wordsworth Editions Ltd, 1997)
This book outlines the fascinating biographical details and often brutal careers of the 200 most outstanding land commanders from the 10th to the 20th century.
Keywords: Biography & Autobiography; Military; Military; Biography & Autobiography; Reference; History